Dungeon club. Roll call - Ostertag, Molly (Harper Alley, 2022)
Jess and her best friend, Olivia, are able to escape the drudgery of middle school through their Dungeons & Dragons game, and together, they are always able to let their imaginations run wild. Olivia runs their game as Dungeon Master, and Jess is the solo party member, a lone-wolf character named Sir Corius. But when Olivia suggests they add new players to their group, Jess isn't so sure she wants to share their game or her best friend. Slowly, Jess starts to warm up to having a larger party, but when a bully at school makes fun of her for hanging out with the new club member, Jess makes a terrible mistake.